Rare and common manifestations of COVID‐19 in children - Cristiana Colonna; Lucia Restano; Nicola A. Monzani; Martina Zussino; Alessandra Ponziani; Stefano Cambiaghi; Riccardo Cavalli (JEADV Clinical Practice, 2022)
Abstract Introduction It has been almost 2 years since the first reports on cutaneous manifestations of COVID‐19. Those reported in children are different and include macular, papular, lichenoid, vesicular, urticarial, and vascular morphologies, among others. The prognosis of isolated cutaneous involvement in COVID‐19 in children is usually self‐limiting but the extreme variety of clinical presentations complicates the clinical approach. Methods Numerous reviews have been systematically drafted and edited giving the clinicians a future direction for skin presentations during pandemics. Results and Discussion Hereby we report the rare and common manifestations of COVID‐19 in children and question the recurrence phenomena and age‐related distribution of the eruptions.